NUMERICAL SOLUTIONS OF THE FRACTIONAL KdV-BURGERS-KURAMOTO EQUATION - Kaya, Dogan; Gulbahar, Sema; Yokus, Asif (Vinca Inst Nuclear Sci, 2018)
Non-linear terms of the time-fractional KdV-Burgers-Kuramoto equation are linearized using by some linearization techniques. Numerical solutions of this equation are obtained with the help of the finite difference methods. Numerical solutions and corresponding analytical solutions are compared. The L-2 and L-infinity error norms are computed. Stability of given method is investigated by using the Von Neumann stability analysis.
Keywords: time fractional KdV-Burgers-Kuramoto equation; finite difference method; stability